2014
DOI: 10.1016/j.ydbio.2014.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Hectd1 is required for development of the junctional zone of the placenta

Abstract: The placenta plays a critical role in the growth and survival of the fetus. Here we demonstrate that the Homologous to the E6-AP Carboxyl Terminus (HECT) domain E3 ubiquitin ligase, Hectd1, is essential for development of the mouse placenta. Hectd1 is widely expressed during placentation with enrichment in trophoblast giant cells (TGCs) and other trophoblast-derived cell subtypes in the junctional and labyrinth zones of the placenta. Disruption of Hectd1 results in mid-gestation lethality and intrauterine grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 55 publications
(89 reference statements)
1
31
0
Order By: Relevance
“…The severe placental defects described here and in our previous study [2] likely contribute to midgestation lethality and IUGR observed in Hectd1 mutants. Other developmental defects in Hectd1 mutants may also play a role such as complex cardiac defects [20], which could exacerbate or even cause placental defects.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…The severe placental defects described here and in our previous study [2] likely contribute to midgestation lethality and IUGR observed in Hectd1 mutants. Other developmental defects in Hectd1 mutants may also play a role such as complex cardiac defects [20], which could exacerbate or even cause placental defects.…”
Section: Discussionsupporting
confidence: 69%
“…Data presented here and in our previous study demonstrate that Hectd1 is essential for development of the murine placenta [19]. Hectd1 is expressed throughout development of this organ and enriched in some labyrinthine trophoblast populations including SynT-I and S-TGC cells [2].…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations